Response surface optimization reveals monthly total flavonoid peaks in Ginkgo biloba leaves with corresponding DPPH scavenging activity - Xiaoyu Shen; Yangjie Lu; Qi Zhu; Yangbo Zhang; Li Zeng (Scientific Reports)
Abstract The study investigated the influence of ethanol concentration, reflux time, and reflux temperature on the content of total flavonoids (TFs) in Ginkgo biloba (GB) leaves. The optimal extraction conditions were determined using the response surface (RS) methodology. The fluctuation of flavonoid content in ethanol extracts of GB leaves across different months was compared with these optimized extraction parameters. Additionally, we investigated the antioxidant activity against DPPH free radicals for the GB extract in the month with the highest flavonoid content. Following RS optimization, the optimal extraction conditions for GB flavonoids were identified as follows: extraction rate of 1.175% at 61 °C for 30 min using 77% ethanol. Under these optimized conditions, the total flavonoid content of GB exhibited a bi-peak pattern, peaking in May and August. The extract obtained in May showed superior DPPH free radical-scavenging ability. These findings provide valuable insights for selecting raw materials for future preparations of GB products.